2015
DOI: 10.1371/journal.ppat.1004679
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Cholesterol Degradation in Mycobacterium tuberculosis Reveal How the Bacterium’s Metabolism Is Constrained by the Intracellular Environment

Abstract: Mycobacterium tuberculosis (Mtb) relies on a specialized set of metabolic pathways to support growth in macrophages. By conducting an extensive, unbiased chemical screen to identify small molecules that inhibit Mtb metabolism within macrophages, we identified a significant number of novel compounds that limit Mtb growth in macrophages and in medium containing cholesterol as the principle carbon source. Based on this observation, we developed a chemical-rescue strategy to identify compounds that target metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
269
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(287 citation statements)
references
References 59 publications
13
269
0
1
Order By: Relevance
“…Building on these observations, an unbiased chemical screen was recently used to identify compounds that inhibit propionate catabolism and thereby diminish M. tuberculosis survival within macrophages. One such compound, V-13-009920, inhibited PrpC and prevented M. tuberculosis growth in cholesterol-containing media [60]. These results highlight the potential of targeting this pathway in prominent human pathogens as an antimicrobial strategy.…”
Section: Propionate Metabolism As An Antimicrobial Targetmentioning
confidence: 80%
See 1 more Smart Citation
“…Building on these observations, an unbiased chemical screen was recently used to identify compounds that inhibit propionate catabolism and thereby diminish M. tuberculosis survival within macrophages. One such compound, V-13-009920, inhibited PrpC and prevented M. tuberculosis growth in cholesterol-containing media [60]. These results highlight the potential of targeting this pathway in prominent human pathogens as an antimicrobial strategy.…”
Section: Propionate Metabolism As An Antimicrobial Targetmentioning
confidence: 80%
“…In support of this, PrpC was found to be required for intracellular growth in macrophages, indicating that propionyl-CoA metabolism is critical for maintaining the intracellular lifestyle [34,58,59]. Indeed, deletion of prpC impaired the ability of M. tuberculosis to grow in media containing cholesterol as a primary carbon source, and recent work has established that an M. tuberculosis prpCD double mutant also exhibits a growth defect in murine bone marrow-derived macrophages [60]. These observations are consistent with the notion that M. tuberculosis obtains a significant amount of its carbon requirements from cholesterol [61].…”
Section: Propionate Metabolism As An Antimicrobial Targetmentioning
confidence: 88%
“…These chemical probes represent new classes of inhibitors that target metabolic pathways required to support growth of Mtb in its host cell. 30 In addition, studies into the mode of action of existing frontline drugs on intracellular Mtb revealed how hostderived stresses contribute to the rise of a drug tolerant phenotype. This does however represent an opportunity for the identification of synergistic inhibitors that could ameliorate existing drug therapies.…”
Section: Session 3: Metabolism Of Intracellular Bacteriamentioning
confidence: 99%
“…Recent studies have shown the value of screening compound libraries under in vivo-like conditions, since M. tuberculosis undergoes profound metabolic shifts during infection, which may alter target vulnerability. Inducing M. tuberculosis dormancy phenotypes in vitro can enrich the discovery of compounds targeting novel and conditionally essential pathways (13)(14)(15)(16)(17)(18). The Wayne model of gradual oxygen depletion is the most well-characterized in vitro dormancy model.…”
mentioning
confidence: 99%